Aspects of enzymatic modification of plant proteins - D. S. Kulikov; A. A. Korolev (Пищевые системы)
Due to the constant increase in population and the growing demand for food products with a high content of biologically valuable protein, there is a growing interest in obtaining such products from sources alternative to animal raw materials. The production of proteins from plant raw materials with high biological value is a promising area for research. Plant proteins have relatively low digestibility and have functional and technological properties that limit their use in food products. To increase digestibility and change the functional and technological properties, plant proteins are modified by chemical, physicochemical and biotechnological methods. The most environmentally friendly and cost-effective is biotechnological processing of raw materials with both the original microorganisms (lactic acid bacteria of the genera Lactobacillus, Staphylococcus, Pediococcus, Enterococcus, Staphylococcus, Micrococcus and Leuconostoc, bacteria of the genus Bacillus, fungi of the genera Aspergillus, Rhizopus, Saccharomyces and Candida spp.) and proteolytic enzyme preparations obtained from them. Enzymatic modification makes it possible to solve the problem of low digestibility of plant proteins, improve their functional and technological properties, reduce allergenicity and neutralize specific taste. Enzymatic modification allows us to solve the problem of low digestibility of plant proteins, their functional and technological properties, reduce allergenicity and neutralize specific taste. In addition, the biotechnological method of modification with microorganisms and enzyme preparations is also used for hydrolysis of proteins to bioactive peptides intended for functional nutrition: with high antioxidant, antitumor, antidiabetic and mineral-binding activity. In the process of modification, it is necessary to take into account the type of enzyme or microorganism used, its concentration, degree of hydrolysis, type of raw material, molecular weight of its proteins and other factors affecting the quality of the obtained hydrolysates and peptides. Otherwise, enzymatic modification causes undesirable changes: a decrease in functional and technological properties and nutritional value, as well as deterioration in organoleptic indicators, in particular an increase in the bitterness of hydrolysates. This review presents an analysis of a wide range of research results of Russian and foreign scientists in recent years in the field of enzymatic modification of plant proteins. The main focus is on obtaining protein hydrolysates and high-quality bioactive peptides that can compete with proteins of animal origin.